2016
DOI: 10.1007/s00011-016-0956-8
|View full text |Cite
|
Sign up to set email alerts
|

VBP15, a novel dissociative steroid compound, reduces NFκB-induced expression of inflammatory cytokines in vitro and symptoms of murine trinitrobenzene sulfonic acid-induced colitis

Abstract: VBP15 may reduce symptoms of IBD, while decreasing or avoiding detrimental side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…[8][9][10][11][12][13] Studies of vamorolone in animal models of chronic inflammatory states, including DMD mouse models, have shown retention of antiinflammatory efficacy and loss of adverse effects compared to prednisolone. 10,12,[14][15][16] The retention of antiinflammatory efficacy and loss of side effects in preclinical models are consistent with vamorolone blocking NF-κBassociated proinflammatory signals as a ligand/receptor monomeric state instead of the traditional molecular models of ligand/receptor dimeric complexes. 17 A phase 1 study of vamorolone in healthy adult men 18 and a 2-week treatment, 2-week washout, 4-week phase 2a study in patients with DMD 19 showed an improved profile of typical glucocorticoid-like safety concerns as measured by serum biomarkers after 2 weeks of treatment.…”
mentioning
confidence: 56%
“…[8][9][10][11][12][13] Studies of vamorolone in animal models of chronic inflammatory states, including DMD mouse models, have shown retention of antiinflammatory efficacy and loss of adverse effects compared to prednisolone. 10,12,[14][15][16] The retention of antiinflammatory efficacy and loss of side effects in preclinical models are consistent with vamorolone blocking NF-κBassociated proinflammatory signals as a ligand/receptor monomeric state instead of the traditional molecular models of ligand/receptor dimeric complexes. 17 A phase 1 study of vamorolone in healthy adult men 18 and a 2-week treatment, 2-week washout, 4-week phase 2a study in patients with DMD 19 showed an improved profile of typical glucocorticoid-like safety concerns as measured by serum biomarkers after 2 weeks of treatment.…”
mentioning
confidence: 56%
“…Vamorolone has shown efficacy similar or superior to prednisone in mouse models of muscular dystrophy [15,23], lung disease [16,19,24], inflammatory bowel disease [18], and multiple sclerosis [17]. These in vivo pre-clinical studies also showed improvement of bone safety profiles of vamorolone when benchmarked against prednisone tested in parallel, including loss of stunting of growth and osteopenia [15,17,18]. Measures of immune suppression were studied both in vitro and in vivo , where CD4 cells declined with prednisone, but not vamorolone [15].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the fact that SCD patients treated with corticosteroids typically suffer adverse events related to vaso-occlusion (increase hospitalization for pain, acute chest syndrome, strokes) might suggest that corticosteroids may alter blood rheology, a hypothesis, which is worthy of testing in future studies. Further, while this preclinical study examined only one level of equipotent doses for prednisolone and vamorolone, which have been shown to be beneficial in mouse models of brain tumor and of inflammatory bowel disease 23 , 26 , it is possible that different doses could have yielded different results. In fact, vamorolone was shown to be well tolerated in healthy adults at doses of up to 20 mg/kg/day in completed phase 1 clinical trials and is in phase 2 clinical trials in patients with Duchenne muscular dystrophy (NCT02760264).…”
Section: Discussionmentioning
confidence: 99%